Layanan Bimbingan dan Konseling dalam Mengembangkan Kematangan Karier Remaja - Azka Dhianti Putri; Mamat Supriatna; Nadia Aulia Nadhirah; Ahmad Rofi Suryahadikusumah (Ma'soem University, 2022)
Irregularity and instability in adolescence organize, acquiring responsibility, and awareness of various careers or occupations become problems for adolescents in reaching the early stages of a career. Other studies that meet that there are adolescents who are in the identity diffusion status, namely adolescents who have never experienced an identity crisis and do not make commitments to their career choices, so they usually do not care about the formation process because they consider it important. Whereas Erikson said that the most important problem faced was the problem of career immaturity. Therefore, there is an ideal condition for adolescents to reach career maturity, and there are still many students who show irregularities and instability in career planning and have discussions of vocational identity status. This article aims to study various guidance and counseling service strategies that can be used by effective guidance and counseling teachers in developing youth careers. The research method of this article uses a qualitative approach with a literature study method through a study of 19 articles and one book. The results obtained are that various career guidance and counseling services can be carried out in basic services, responsive services, individual planning, and system support.